Phát biểu khai mạc của Chủ tịch Quốc hội Vương Đình Huệ tại Kỳ họp thứ 6, Quốc hội khóa XV (Sáng ngày 23/10/2023) (2023)
Toàn văn Phát biểu khai mạc của Chủ tịch Quốc hội Vương Đình Huệ tại Kỳ họp thứ 6, Quốc hội khóa XV (Sáng ngày 23/10/2023).